Genetics of Seed Yield Attributes and Oil Contents in Brassica rapa L. - Razzaq, Humera; Chouhdary, Laraib; Ul Hassan, Waqar; Zia, Muhammad Ali; Amjad, Noreen; Kanwal, Shamsa (Integrative Plant Biotechnology, 2025)
Brassica rapa L. has become a promising crop to sustainable agricultural and industrial growth since reliance on imports goes up and biofuel is in demand. The current work dissected the variability in genetic aspects including ability, heterosis and heritability to seed yield and traits concerned with oil which provide new information in developing hybrids. Eleven high performing accessions were identified as female lines and three low yielding accessions were identified as testers and 33 F1 hybrids were produced in Line×Tester mating plan. The hybridization was controlled in 2022-23, and then the evaluation in the field was carried out in 2023-24 based on a randomized complete block design that had three replications. There was significant difference between parental lines and hybrids. Line 25052 showed high general combining ability (GCA) on average on various traits and the tester ORL1 had a positive effect in the branching, early flowering and seed productivity. Cross 25052×ORL1 was one of the best hybrids with high specific combining ability (SCA) and great level of heterosis, as it showed high levels of plant height, number of siliques, yield of seed per plant and oil content in both years of experimentation. In a similar manner, cross 25037×ORL3 and 25042×ORL3 were found to have significant SCA effects and heterotic expression, further supporting the fact of non-additive action of gene in hybrid vigor. Estimates of hereditability showed that quality-related traits (especially oil content and 100-seed weight) were largely under the influence of additive genetic effects, which ensured meritorious enhancement by means of breeding. Conversely, additive and dominance gene effects manifested in yield-related traits, thus explaining the relevance of the properties in breeding on heterosis. The results highly suggest a potential of cross 25052×ORL1 to improve yield and simultaneously enhance the quality of the oil in B. rapa. Its stability over the years of the experiments proves that it can be further developed into multi-location trials. This research, in addition to the direct implications of breeding, provides a set of breeding variances to be exploited in breeding breeds of B. rapa, which eventually result in the generation of high-yielding and high-oil content coupled with climate-tolerant crops to decrease dependence on imports and enhance the sustainability of agriculture.